Anatomical Variations of the Renal Artery: A Cross-Sectional Cadaveric Study - Umeshwar Prasad Thakur; Pranav Kumar Yadav; Tirtha Narayan Shah; Abdullah Rain; Chandrajeet Kumar Yadav; Ravindra Khadka (Janaki Medical College Journal of Medical Science, 2025)
Background & Objectives: The renal arteries are the primary blood supply to the kidneys and usually arise as single branches from the abdominal aorta at the L1–L2 level. However, variations in their number, origin, and branching pattern are common and carry important implications for renal transplantation, vascular surgery, and interventional radiology. This study aimed to document anatomical variations of renal arteries in cadaveric specimens with respect to their number, level of origin, source of accessory arteries, and length. Materials and Methods: An observational cross-sectional study was conducted on 32 kidneys from 16 formalin-fixed cadavers during routine dissection sessions at the Department of Anatomy, Karnali Academy of Health Sciences, Jumla. Renal arteries were dissected to trace their origin, course, and branching pattern. Variations were recorded, artery lengths were measured with a Vernier caliper, and representative findings were photographed. Data were analyzed descriptively. Results: Out of 32 kidneys, 27 (84.37%) had a single renal artery, while 5 (15.62%) had double arteries, more common on the left side (9.37%) than the right (6.25%). Renal arteries originated at the same level in 56.25% of specimens, while a higher origin was more frequent on the right (25%) compared with the left (9.37%). All main renal arteries arose from the aorta. Accessory arteries originated either from the aorta (35.71%) or from the main renal artery (64.28%). Artery lengths ranged from 0.8 to 5.6 cm, with the right consistently longer than the left. Conclusions: Renal arteries demonstrated considerable anatomical variation in number, origin, and length. Awareness of these variations is crucial to minimize complications in surgical and interventional procedures involving the kidneys.